Beyond the Dutch Quota: Media Policy and Cultural Diversity in Local Video-on-Demand Production (2013–2023) - Berber Hagedoorn; Sandra Becker (Media and Communication)
Starting January 1, 2024, a new Dutch investment obligation requires that streaming services with annual revenues exceeding 10 million euros allocate 5% of their turnover to Dutch content production. This policy aligns with similar obligations in countries like France, Germany, and Italy, which introduced tax-based investment obligations for streaming platforms before the 2018 revision of the EU’s Audiovisual Media Service Directive (AVMSD). The AVMSD established a 30% European content quota for subscription video-on-demand (SVoD) platforms and permitted member states to implement revenue-based investment obligations to support local industries. Our article situates the Netherlands as a small-screen media industry and the base of Netflix’s first European headquarters. We contextualise the Dutch investment obligation within the evolving European media landscape, examining shifts in diversity and inclusion in Dutch VoD fiction productions from 2013 to 2023. We assess production trends by type and genre by critically analysing policy frameworks and production data from international SVoD platforms (e.g., Netflix, Amazon Prime, Disney+) and domestic steaming services (Videoland, NPO Start/Plus). Our findings reveal significant gaps in genre diversity and underinvestment in high-cost historical dramas and fantasy/horror/sci-fi series, highlighting a decade-long reliance on mainstream-oriented genres, including drama and crime series. This context underscores the importance of the new regulation in addressing these disparities and critically examines the requirements of the new regulation. Our article contributes to understanding the state of Dutch VoD production and evaluates the potential of the investment obligation to foster cultural and genre diversity in Dutch VoD fiction.